Spring staging areas of White-fronted Geese in West Greenland - Glahder, C M; Fox, A D; Walsh, A J (Wildfowl, 2014)
During spr ing 1998 and 1999, 10 Greenland White-fronted Geese fitted with satellite t ra n smitte rs on the w in ter ing grounds at Wexford, Ireland, migrated to West Greenland and provided new in fo rma t io n on spring staging areas and staging periods.